Campus Canopy, 1950-01-21 - The Campus Canopy, Valdosta State College (Valdosta State College, 1950)
Norton, Mann, Griffin, Zeigler Named Margas -- Chancelor Declares GSWC Co-ed; Becomes Valdosta State in September
Valdosta State College's Student Newspaper
Keywords: Valdosta State University -- Periodicals